PEMANFAATAN ABU ENCENG GONDOK DAN PENGARUHNYA TERHADAP KARAKTERISTIK BATAKO - Nur Aisyah Jalali, Khairil (Universitas Negeri Yogyakarta, 2016)
ABSTRACTThis study aims to utilize water hyacinth in the manufacture of concrete blocks and add insight about technologyash bricks using water hyacinth as an added ingredient. Test specimen in the form of brick or concrete hollowbrick measuring 40x20x10 cm made from a mixture of cement, sand and water with the composition 1: 4 (ratio byvolume). Ingredients added in the form of ash water hyacinth (AEG) drying and firing the result of water hyacinthstems. Variations of the test specimen consists of a brick without AEG, AEG and adobe with the addition of up to25% every 5% increase in the volume of semen. The test includes examining the size, the compressive strengthtesting, and water absorption adobe. The measurement results showed that the length, width, and thickness ofbrick still within the limits allowed for all specimens. The test results an average compressive strength of concreteblocks shows that the higher the levels of AEG, the average compressive strength of concrete blocks began todecline. Based Research and Development Infrastructure (2003b), brick by AEG level of 5% into the quality of III,the levels of 10% and 15% included in the grade IV, while levels of 20% and 25% are not included in allcategories. The test results of water absorption in the brick does not show a regular trend. According to theResearch and Development Infrastructure (2003b), brick on all variations are included in all of the quality due tomoisture absorption that occurs less than 25% (quality I) and 35% (quality II).Keywords: hyacinth, brick, size, compressive strength,water absorptionABSTRAKPenelitian ini bertujuan untuk memanfaatkan enceng gondok pada pembuatan batako dan menambah wawasantentang teknologi batako yang menggunakan abu enceng gondok sebagai bahan tambah. Benda uji berupabatako atau bata beton berlubang berukuran 40x20x10 cm yang dibuat dari campuran semen, pasir, dan airdengan komposisi 1:4 (perbandingan volume). Bahan tambah berupa abu enceng gondok (AEG) hasilpengeringan dan pembakaran batang enceng gondok. Variasi benda uji terdiri atas batako tanpa AEG, danbatako dengan penambahan AEG hingga 25% setiap kenaikan 5% terhadap volume semen. Pengujian meliputipemeriksaan ukuran, pengujian kuat tekan, dan penyerapan air batako. Hasil pengukuran menunjukkan bahwaukuran panjang, lebar, dan tebal batako masih berada dalam batas yang diperkenankan untuk semua benda uji.Hasil pengujian kuat tekan rata-rata batako menunjukkan bahwa semakin tinggi kadar AEG, maka kuat tekanrata-rata batako semakin turun. Berdasarkan Balitbang Kimpraswil (2003b), batako dengan kadar AEG 5%masuk dalam mutu III, kadar 10% dan 15% masuk dalam mutu IV, sedangkan kadar 20% dan 25% tidak masukdalam semua kategori. Hasil pengujian penyerapan air dalam batako tidak menunjukkan tren yang teratur.Menurut Balitbang Kimpraswil (2003b), batako pada semua variasi tidak masuk dalam semua mutu karenapenyerapan air yang terjadi kurang dari 25% (mutu I) dan 35% (mutu II).Kata kunci: batako, enceng gondok, kuat tekan, penyerapan air, ukuran